Mucosal-Associated Microbiota Other Than Luminal Microbiota Has a Close Relationship With Diarrhea-Predominant Irritable Bowel Syndrome - Yang, Min; Hong, Gaichao; Jin, Yu; Li, Ying; Li, Gangping; Hou, Xiaohua (Frontiers in Cellular and Infection Microbiology, 2020)
Studies have linked dysbiosis of gut microbiota to irritable bowel syndrome (IBS), However, dysbiosis only referring to structural changes without functional alteration or focusing on luminal microbiota are incomplete. To fully investigate the relationship between gut microbiota and clinical symptoms of Irritable Bowel Syndrome with Diarrhea (IBS-D), fecal samples and rectal mucosal biopsies were collected from 69 IBS-D patients and 20 healthy controls (HCs) before and during endoscopy without bowel preparation. 16S rRNA genes were amplified and sequenced, and QIIME pipeline was used to process the composition of microbial communities. PICRUSt was used to predict and categorize microbial function. The composition of mucosal-associated microbiota (MAM) was significantly different in IBS-D patients compared to HCs; while no difference in luminal microbiota (LM). MAM, but not LM, was significantly positively correlated with abdominal pain and bloating. A greater number of MAM functional genes changed in IBS-D patients than that of LM compared with HCs. Metabolic alteration in MAM not in LM was related with abdominal pain and bloating. There was a close relationship between the composition and function of MAM and clinical symptoms in IBS-D patients which suggest the important role of MAM in pathogenesis and therapies in IBS-D and it should be highlighted in the future.